2015
DOI: 10.3892/mmr.2015.3643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide synthase deficiency on a disintegrin and metalloproteinase domain-containing protein 12 expression in mouse brain samples

Abstract: Abstract.A d isi nt eg r i n a nd met a l loprot ei nase domain-containing protein 12 (ADAM12) belongs to the ADAM family of transmembrane proteins. Via proteolysis, cell adhesion, cell-cell fusion, cell-matrix interaction and membrane protein shedding, ADAM proteins are involved in normal brain development, and also in cancer genesis and progression, and in inflammation. Therefore, neurobiological research focusing on this protein is increasing. Nitric oxide (NO), which is endogenously produced by NO synthase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…[63,64] A disintegrin and metalloproteinase-12 (ADAM12) is a cell-surface glycoprotein containing metalloprotease, disintegrin, cysteine-rich and EGF-like domains which possess cell-binding and metalloprotease properties. ADAM12 is able to release of the extracellular parts of membrane-bound proteins, including glycoprotein non-metastatic melanoma protein B and basigin, heparin-binding-EGF, insulin-like growth factor 2-binding proteins 3 and 5, and oxytocinase [65][66][67][68]. It is reported that ADAM12 is predominantly localized in white and gray matter oligodendrocytes of rat and human CNS.…”
Section: Rt-pcr Western Blot Analysis Immunohistochemistrymentioning
confidence: 99%
“…[63,64] A disintegrin and metalloproteinase-12 (ADAM12) is a cell-surface glycoprotein containing metalloprotease, disintegrin, cysteine-rich and EGF-like domains which possess cell-binding and metalloprotease properties. ADAM12 is able to release of the extracellular parts of membrane-bound proteins, including glycoprotein non-metastatic melanoma protein B and basigin, heparin-binding-EGF, insulin-like growth factor 2-binding proteins 3 and 5, and oxytocinase [65][66][67][68]. It is reported that ADAM12 is predominantly localized in white and gray matter oligodendrocytes of rat and human CNS.…”
Section: Rt-pcr Western Blot Analysis Immunohistochemistrymentioning
confidence: 99%